Attention Bias Modification Treatment for Adolescents With Social Anxiety Disorder. Issue 1 (January 2019) - Ollendick, Thomas H.; White, Susan W.; Richey, John; Kim-Spoon, Jungmeen; Ryan, Sarah M.; Wieckowski, Andrea Trubanova; Coffman, Marika C.; Elias, Rebecca; Strege, Marlene V.; Capriola-Hall, Nicole N.; Smith, Maria
Abstract: Social anxiety disorder (SAD) tends to emerge during the early teenage years and is particularly refractory to change even when standard evidence-based CBT treatments are delivered. Efforts have been made to develop novel, mechanistic-driven interventions for this disorder. In the present study, we examined Attention Bias Modification Treatment (ABMT) for youth with SAD. Participants were 58 adolescents (mean age = 14.29 years) who met diagnostic criteria for SAD and who were randomized to ABMT or a placebo control condition, Attention Control Training (ACT). We predicted that ABMT would result in greater changes in both threat biases and social anxiety symptoms. We also explored potential moderators of change including the severity of social anxiety symptoms, the level of threat bias at pretreatment, and the degree of temperament-defined attention control. Contrary to our hypotheses, changes in attention bias were not observed in either condition, changes in social anxiety symptoms and diagnosis were small, and significant differences were not observed between the ABMT and ACT conditions. Little support for the proposed moderators was obtained. Reasons for our failure to find support for ABMT and its potential moderators are explored and recommendations for changes in the ABMT paradigm are suggested. Highlights: We compared Attention Bias Modification Treatment to a control for youth with SAD No differences in ABMT and the control in reducing social anxiety or attention bias Need for modifications within ABMT to enhance salutatory effects for SAD